ASSESSMENT OF PROBLEM-SOLVING SKILLS IN THE TOPIC OF ENVIRONMENT: ITS VALIDITY AND RELIABILITY - Asmaul Lutfauziah; Aris Handriyan; Fifi Khoirul Fitriyah (Program Studi Pendidikan IPA, Fakultas Ilmu Pendidikan, Universitas Trunojoyo Madura, 2023)
This study aims to determine the validity and reliability of the instrument for assessing problem-solving skills in the topic of environment. This research includes in a research and development of test instruments with the ADDIE model, namely analysis, design, development, implementation, and evaluation. The instrument that had been made was then tested on 31 students at the Islamic Boarding School of Jagad 'Alimussirry, Surabaya. The data were analyzed for its validity and reliability. The validity was measured using the Pearson product-moment correlation coefficient test. The reliability test used Cronbach's alpha test. The results of the study show that all items are valid and reliable in the high category. The percentage of eligibility from experts (material experts, education experts, and education practitioners) is 89% with a very decent category so this instrument is declared suitable to be used to measure problem-solving skills. This instrument contains five stages of problem-solving, namely identifying problems, determining solutions, planning solutions, implementing solutions, and evaluating the results of problem-solving. The problems identified consist of two kinds, namely social problems and physical problems in Islamic boarding schools. To conclude, the problem-solving skills assessment can be used by students to improve the abilities in analyzing problems.